“Sandwich” mesh reconstruction of female giant urethral diverticulum: a case report - Xie, Juanjuan (BMC Urol, 2020)
BACKGROUND: There is no consensus between urologists on the diagnosis and treatment of female urethral diverticula. Once the diagnosis has been established, the most common treatment approach is surgical excision and reconstruction. Whether a staged procedure or simultaneous management is more appropriate for treating concomitant urethral diverticula and stress urinary incontinence remains controversial. CASE PRESENTATION: A 63-year-old woman was hospitalized for repeated frequent urination, urgent urination, odynuria, and dysuria accompanied by intermittent overflow urinary incontinence for over 10 years. She had a 5 year history of urinary stress incontinence prior to onset of these symptoms and had had four urethral caruncles resected on four separate occasions. There was visible leakage of urine when abdominal pressure was increased during physical examination and urodynamic studies. Additionally, turbid urine was discharged when the anterior vaginal wall was squeezed. Cystourethrography showed circumferential filling with contrast and multiple bladder diverticulae in the mid plane of the pubic symphysis. Urethrocystoscopy showed an orifice to a diverticulum at 7 o’clock in the proximal urethra, into which an F19.8 urethroscope could be inserted, enabling examination of most of the diverticulae. The urethral diverticulae were resected, followed by mesh reconstruction of the urethra. During a 20-month follow-up, the treatment outcomes were satisfactory. CONCLUSION: We here report a case of a giant circumferential urethral diverticulum combined with stress urinary incontinence that was successfully managed by an uncommon surgical reconstructive technique: a minimally invasive “Sandwich” mesh repair procedure utilizing synthetic mesh wrap in the midurethral region.